Cryopreservation of mithun semen: comparative study of conventional vs controlled freezing - KHAN, M H; SINHA, PAPIYA; PERUMAL, P; HAZARIKA, S B (The Indian Journal of Animal Sciences, 2017)
In this present study, 2 different semen freezing techniques (conventional and controlled freezing) for cryopreservation of mithun semen were compared with regard to post-thaw sperm characteristics. Pooled ejaculates (10) of mithun semen were utilized for the present study. Each ejaculate was aliquoted into 2 and extended with tris egg yolk citrate glycerol (TEYG) extender and freezing was done with conventional method as well as through programmed freezer using 0.5 ml straw. Semen samples were evaluated for sperm motility, liveability, acrosome integrity, plasma-membrane integrity and sperm abnormalities both in fresh and frozen semen. Though there was nonsignificant difference in post-thaw sperm motility and liveability; however, acrosome and plasma-membrane integrity were significantly higher in conventional freezing method as compared to that in controlled freezing method.